Increased Expression of 9-Cis-Epoxycarotenoid Dioxygenase, PtNCED1, Associated With Inhibited Seed Germination in a Terrestrial Orchid, Phaius tankervilliae - Lee, Yung-I.; Chen, Ming-Chuan; Lin, Li; Chung, Mei-Chu; Leu, Wei-Ming (Frontiers in Plant Science, 2018)
The phytohormone abscisic acid (ABA) is involved in regulating seed dormancy and germination. A crucial step of ABA biosynthesis in higher plants is the oxidative cleavage of cis-epoxycarotenoids by 9-cis-epoxycarotenoid dioxygenase (NCED). Seed development in orchids is unusual because the embryos are minute in size, without obvious histodifferentiation, and lack endosperm. To understand the regulation of ABA biosynthesis in orchid seeds, we isolated and characterized a full-length cDNA encoding an NCED homologue, PtNCED1, from developing seeds of an ornamental orchid, Phaius tankervilliae. Germination percentage was high at 90 days after pollination (DAP), when a globular embryo proper with a degenerating suspensor was evident. After 90 DAP, seed maturation was accompanied by a decrease in water content and a concomitant increase in ABA content and PtNCED1 mRNA level along with a marked decrease in germination percentage. Mature seeds pretreated with NaOCl solution lowered ABA content and improved seed germination. Moreover, after seed germination, developing protocorms could respond to dehydration stress. Dehydration of protocorms stimulated an increase in PtNCED1 level along with ABA content. Our results provide evidence of the involvement of PtNCED1 in regulating endogenous ABA content in developing seeds and protocorms. The accumulation of endogenous ABA content in orchid seeds may have a critical role in seed dormancy and the protocorm response to water stress after seed germination.